Chapter Cambiare opinione (o quasi) su Camilleri - TRAINA, Giuseppe (Biblioteca di Studi di Filologia Moderna, 2022)
The author takes the opportunity of the celebrations in honor of Annamaria Pagliaro to return to the works of Andrea Camilleri, confirming some perplexities already expressed in an article from 1998, especially regarding his detective novels. On other aspects of Camilleri's works, however, the author's opinions have changed. In this new critical work, the author took into account the works subsequently published by Camilleri, especially the narrative masterpiece Il re di Girgenti, but also his public role and the relationship he was able to establish with his faithful readers.